2015
DOI: 10.1111/bpa.12254
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Serine 727 Phosphorylation: A Relevant Target to Radiosensitize Human Glioblastoma

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 63 publications
2
25
0
Order By: Relevance
“…Moreover, this study of Lin et al evidenced a statistically significant association of pSTAT3-S727 and pSTAT3-Y705 [152]. In a cohort of 30 GBM clinical specimens and a panel of 15 GBM cell lines, we showed that pSTAT3-S727 is present in all studied human malignant glioma cell lines and all the examined GBM specimens [153]. However, pSTAT3-Y705 was not detected in some GBM cell lines or specimens and was moreover restricted to a variable number of GBM cells in the positive clinical samples.…”
Section: Constitutive Phosphorylation Of Stat3-s727supporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, this study of Lin et al evidenced a statistically significant association of pSTAT3-S727 and pSTAT3-Y705 [152]. In a cohort of 30 GBM clinical specimens and a panel of 15 GBM cell lines, we showed that pSTAT3-S727 is present in all studied human malignant glioma cell lines and all the examined GBM specimens [153]. However, pSTAT3-Y705 was not detected in some GBM cell lines or specimens and was moreover restricted to a variable number of GBM cells in the positive clinical samples.…”
Section: Constitutive Phosphorylation Of Stat3-s727supporting
confidence: 67%
“…Moreover, increased expression of the both makes worse the clinical outcome [152]. Since, pSTAT3-Y705 is not detected is some glioma specimens and does not accumulate in all glioma neoplastic cells [153], we speculate that it is not a major driver of GBM aggressiveness. In contrast, pSTAT3-S727 detected is all neoplastic cells of all GBM specimens may be a best prognostic marker, provided that a discriminative detection assay is performed.…”
Section: Stat3 and Prognosismentioning
confidence: 88%
“…It seems that preexisting STAT3 activity in MDSCs, can skew TLR9 signaling toward supporting tumor angiogenesis while blocking antitumor immunity [48][49][50] Recently, TLR9 stimulation by CpG-ODN has been shown to activate NF-kB pathway, leading to Th1 immunostimulation and antitumor immune responses [51,52]. A promising targeted combined therapy should associate T-cell therapy and STAT3 inhibitors linked to CpG/TLR9 that could silence STAT3 in cancer cells and stromal /immune cells and favor down-regulation of cancer stem cells and antitumor immune responses [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…In case of glioblastoma (GBM) high levels of pS727 STAT3 leads to shorter progress free survival [73]. Increased level of pS727 STAT3 in GMB cell lines correlates with the increased intrinsic radioresistance nature and treatment with Gö6976 inhibitor induces radiosensitization in those GBM cell lines that had high levels of pS727 STAT3 and no or weak expression of pY705 STAT3 [74]. The differential role of pS727 and pY705 STAT3 is also seen in deciding the fate of mouse embryonic stem cells (mESC).…”
Section: Ps727 Phosphorylation and K685 Acetylation Of Stat3: The Nonmentioning
confidence: 99%